Land and Military: Legal Aspects of Land Ownership and Utilization for National Defense (RechtJiva, 2025)
This study examines the legal relationship between land ownership, utilization, and national defense in Indonesia, emphasizing how military institutions manage and control land for defense purposes. The research highlights the intersection between agrarian law and defense law, identifying conflicts between state authority, public interest, and community rights. Using a normative juridical and conceptual approach, the study analyzes statutory provisions under Law No. 3 of 2002 on State Defense, Law No. 34 of 2004 on the Indonesian National Armed Forces (TNI), and Law No. 5 of 1960 on Basic Agrarian Principles (UUPA). The findings reveal that while the state holds ultimate control over defense lands (tanah pertahanan), overlapping administrative jurisdictions and the absence of integrated spatial regulations often lead to disputes between military institutions and civilians. Strengthening legal certainty requires harmonization among the Ministry of Defense, National Land Agency (BPN), and local governments to ensure that land management for defense respects both national security and community welfare.